Ethnomathematics in Buying And Selling Transactions of Cracker Traders at Puger Market - Khoiroh, Jazilatul; Putra, Eric Dwi; Murtinasari, Frida (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
This study examines the application of ethnomathematics in the buying and selling transactions of cracker traders at Puger Market, Jember Regency. Ethnomathematics is a study that integrates mathematical elements with community culture. The purpose of this study is to identify how mathematical practices, particularly arithmetic operations such as addition, subtraction, multiplication, and division, are applied contextually by traders in their daily economic activities. This study uses ethnography with a descriptive approach, collecting data through observation, interviews, and documentation. The results show that traders are able to calculate prices and change manually quickly and accurately, even without formal mathematics education. This suggests that the practice of counting in trading activities reflects the real application of mathematical concepts in everyday life and can be used as a source of contextual learning in schools.